[PP.01.23] HIGH UPSTROKE TIME OF ARTERIAL PULSE WAVE IS AN INDEPENDENT PREDICTOR FOR THE PRESENCE AND SEVERITY OF CORONARY ARTERY DISEASE IN OLDER POPULATION. (September 2017) - Shoji, T.; Okada, S.; Ohno, Y.; Nakagomi, A.; Kobayashi, Y.
Abstract : Objective: Ankle–brachial index (ABI) is widely used to screen for the presence and severity of peripheral arterial disease. Upstroke time (UT), a time from the onset to the peak of the arterial pulse wave, is calculated during ABI measurement and serves as an auxiliary index of PAD. UT was also reported to be associated with coronary artery calcification score by multi-detector computed tomography. However, there are no studies examining relationship between UT and coronary sclerosis by invasive coronary angiography (CAG). The aim of this study was to examine the association between UT and the presence and severity of coronary artery disease (CAD) as assessed by CAG. Design and method: We enrolled 304 patients who underwent both ABI measurement and elective CAG for suspected CAD. Significant CAD (sCAD) was defined as having at least one stenotic lesion over 50%. Using univariate and multivariate logistic regression analysis, we evaluated the contribution of UT for the presence of sCAD. In patients with any CAD, relationship between UT and Gensini score was also examined. Results: 134 patients (44.1%) had significant CAD. In the CAD group, UT was higher than in the non-CAD group (CAD vs non-CAD, 156.9 ± 32.1ms vs 147.7 ± 24.0ms, P = 0.005). In both univariate and multivariate logistic regression analyses, UT was associated with sCAD (univariate, Odds Ratio(OR) 1.13[95% Confidence Interval (95% CI) 1.02–1.22], P = 0.015; multivariate, OR 1.18 [95% CI 1.07–1.31], P = 0.001). As the age-related distribution of UT showed quadratic curve, we subdivided the patients at the age of 60. In patients > 60 years (n = 232), both univariate and multivariate analysis demonstrated that UT was associated with sCAD (univariate, OR 1.37[95% CI 1.14–1.64]; multivariate, OR = 1.16 [95% CI 1.02–1.32], all P < 0.05). There was no association among patients < 60years (n = 72). In older patients, multivariate linear regression analysis showed significant correlation between UT and both Gensini and SYNTAX scores (Gensini; Coefficient 2.10, P = 0.002, SYNTAX; Coefficient 0.57, P = 0.039). No correlation was found in younger patients. Conclusions: UT serves as independent, incremental risk for the presence and severity of CAD only in patients aged > 60 years.